Export-led growth and the geopolitical hypothesis: Israel's regime change after the second Intifada - Arie Krampf (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
In recent decades, neo-mercantilism has become a fashionable trend. The appeal of an export-led growth regime is often explained based on the material interests of the domestic growth coalition. This article offers an alternative explanation based on the geopolitical territorial interests of the state. It argues that states may endorse an export-led growth model not because of the demands of social groups but because the political elite believes a neo-mercantilist strategy is more consistent with the state's geopolitical preferences. The article defines this claim as the geopolitical hypothesis of regime change. The geopolitical hypothesis does not imply that social groups are irrelevant to the process. Social groups, the article argues, can play the role of ex-ante transformative actors or of ex-post stabilizing actors. Whereas society-centered theories underline the ex-ante transformative role of social groups, the geopolitical hypothesis argues that social groups can also play an ex-post stabilizing role. Based on the case of Israel, the article argues that during the early 2000s, after the outbreak of the second Intifada, Israel shifted from a consumption-led growth regime to an export-led growth regime. The transition, the article argues, was driven by the hawkish political elite, which prioritized nationalist objectives associated with the continuation and expansion of the occupation. The article concludes by arguing that the case of Israel is exemplary and not unique and that the geopolitical hypothesis can explain the adoption of export-led growth models in other cases.
Keywords: O53; O43; N15; E12; 330; Export-led growth strategy; neo-mercantilism; growth coalition; territorial logic of capitalism